APOLO-Bari, an internet-based program for longitudinal support of bariatric surgery patients: study protocol for a randomized controlled trial - Conceição, Eva Martins (2016)
Background: Despite evidence of successful weight loss for bariatric surgery patients, some patients experience considerable weight regain over the long term. Given the strong association between post-surgery health behaviors and outcomes, aftercare intervention to address key behaviors appears to be a reasonable relapse-prevention strategy. As the burden of obesity rates increases in healthcare centers, an internet-based program appears to be a reasonable strategy for supporting bariatric surgery patients in the long term. The primary purpose of the current project is to develop and test the efficacy and perceived utility of APOLO-Bari.Methods/design: This study is a randomized control trial, which will be conducted in two hospital centers in the North of Portugal; it includes a control group receiving treatment as usual and an intervention group receiving the APOLO-Bari program for one year in addition to treatment as usual. A total of 180 male and female participants who underwent bariatric surgery (gastric sleeve or gastric bypass surgery) for 12 to 20 months will be recruited. Both groups will complete a similar set of questionnaires at baseline, every 4 months until the end of the intervention, and at 6 and 12 months follow-up. Assessment includes anthropometric variables and psychological self-report measures. The primary outcome measure will be weight regain measured at the end of treatment, and at 6 and 12 months follow-up. The secondary aims are to test the cost-effectiveness of the intervention and to investigate psychological predictors and trajectories of weight regain. APOLO-Bari was developed to address the weight regain problem in the bariatric population by offering additional guidance to bariatric patients during the postoperative period. The program includes: (a) a psychoeducational cognitive-behavioral-based self-help manual, (b) a weekly feedback messaging system that sends a feedback statement related to information reported by the participant, and (c) interactive chat sessions scheduled wit